Commercially Available Vitamin A Palmitate is Toxic and Teratogenic to the Tadpoles of Microhyla nilphamariensis (Anura: Microhylidae) - Mahapatra, Cuckoo; Naik, Pranati; Singh, Mandakini; Mohapatra, Pratyush Paradarsita (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: The present study, examined the impact of excess Vitamin A on feeding and pre-metamorphic tadpoles of Microhyla nilphamariensis to analyse its dose-dependent and stage-specific lethal and teratogenic effects. Materials and Methods: Feeding and pre-metamorphic stage tadpoles were subjected to varying concentrations of commercially available Vitamin A palmitate for different time intervals. The control and treated tadpoles were fixed 5, 10- and 15-Days Post Treatment (dpt) in neutral buffered formalin for morphological analyses, morphometry and histology. Results: In both feeding and pre-metamorphic stages, mortality was high when exposed to higher concentrations and longer duration (48–96 hr). When exposed for 24 hr, the treated tadpoles showed significant differences in morphometry, and abnormalities in the eye and intestine of the feeding stages and eye and kidneys of pre-metamorphic stages. Significantly, most of the treated tadpoles died before attaining metamorphosis and those that survived had a delayed metamorphosis with abnormalities. Conclusion: Vitamin A is lethal to the tadpoles of Microhyla nilphamariensis at high concentrations and at lower concentrations it affects the thyroid hormone function and causes abnormalities of various kinds.
Keywords: Tadpoles; Feeding stage; Pre-metamorphic stage; Histology; Morphometry